Data Mining for Decision Making System Determining Web-Based Class Promotion (Case Study: SMK Tarunatama Getasan) - Yonsi Rendra Hanggawan; Suprihadi Suprihadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In this study we want to make an application to predict student graduation, where with the existence of We hope that this application will make it easier and there will be transparency in the graduation system. The method used is to use the C4.5 algorithm which is implemented in the form of WEB, where the algorithm will be processed in the form of PHP. The result of the application made is whether the student passed or not.